Blended skill bagi Pustakawan Akademik dalam menghadapi era Revolusi Industri - Kalarensi Naibaho (Jurnal Pustakawan Indonesia, 2018)
The fourth industrial revolution is considered as a result of the convergence of a number of technologies in industrial operations. These technologies include, but are not limited to robotics, artificial intelligence, big data, 3D printing, biotechnology and technology integration with the human body. Fourth generation industrial revolution is characterized by the emergence of supercomputers, smart robots, vehicles without drivers, genetic editing and neurotechnology development which allows humans to further optimize brain function. Unlike the previous era where competition was marked by 'big vs. small', the 4.0 industrial revolution was characterized by 'fast vs. slow' jargon. Competition in the industrial world no longer depends on the size of the company, but how fast and creative business people see opportunities. This concept does not only occur in the industrial world but also affects the education sector, and the library. The emergence of the trend of e-resources has changed many things in the world of libraries, not only regarding access but also the role of librarians. The convergence of information technology with communication technology causes information and communication technology (ICT) to have an impact on the emergence of the modern library digital landscape. The paradigm shift in the librarian profession is suspected to be the result of the ICT revolution. The speed of change has created a new role for librarians in terms of services and activities, which in turn has an impact on the roles, competencies, skills and knowledge of librarian professionals. The ever-changing information needs of users bring an expansion and new role for librarians to equip themselves with various skills to remain relevant to the digital environment. Blended skills become a familier concept among librarians today. This concept requires many skills that must synergize with institutions or the surrounding environment. Blended librarians are a necessity and librarians must be able to implement in their respective environments. Keyword: Blended librarians, Blended skills, Future librarians, Fourth industrial revolution